Estudo da máquina de indução trifásica operando com tensões desequilibradas e distorcidas - Severo, Dhébora Sayonara de Morais (2020)
This work applies harmonic distortions and voltage unbalances at the supply voltage of threephase induction motor in order to analyze the behavior of voltages and currents under such scenarios and calculates power, distortions and power factors for these simulations on the motor free of load. This analysis is important because the motors consume a large part of the electric energy generated and these are directly affected by the poor quality of energy. Definitions of voltage unbalances and harmonic distortions are presented, besides to the normative aspects that regulate the acceptable limits for these disturbances on the power grid. In the sequence, the modified equivalent model of three-phase induction motor is presented and the effects that it suffers are mentioned, such as increase in temperature, decrease in performance and reduction of life cycle. Then, some power calculation studies are analyzed under unbalances and harmonic distortions. Besides that, the motor equivalent model parameters are corrected. Finally, details are given of the elements used on the data acquisition bench and the results obtained for each of the tests.